Program "Lambangan Melek Aksara" sebagai Peningkatan Kualitas Membaca Anak di Desa Lambangan, Kec. Undaan, Kab. Kudus - Muhammad Arif; Nabila Minhatusaniyah; Mahesa Hendra Yoga; Yusriyyah Adibah; Hasanah Nur Ani; Sinta Dewi Purwanti; Retno Wulan Ndari; Ruly Habibah Al Ihsani; Noor Khoni'ah; Daniswara Agung Pramana; Asep Purwo Yudi Utomo (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The problem of children's reading ability in Lambangan Village, especially first to third grade SD/MI students, is a problem that requires serious attention. The implementation of the "Lambangan Melek AKsara" program is carried out in three stages, namely: preparation, implementation and evaluation. Team UNNES Giat 9 Lambangan Community Service Team uses the EGRA (Early Grade Reading Assessment) test method to assess students' reading abilities. This test was carried out twice, namely before and after the implementation of the "Literacy Symbol" program. As for the implementation of reading training, the team used the learning by playing method. In the first treatment, team UNNES GIAT 9 Lambangan team provided reading teaching) with a focus on recognizing letters and sounds. In the second treatment the focus was on developing students' ability to read and write simple words. In the third treatment, the focus of training shifted to the ability to read simple sentences and understand text. Students' reading ability has improved quite well with this program. Based on a comparison of the results of the first and second EGRA (Early Grade Reading Assessment) tests, students' reading abilities have increased quite significantly. The author hopes that this program can be implemented in other villages throughout Indonesia